2013
DOI: 10.1186/1756-3305-6-92
|View full text |Cite
|
Sign up to set email alerts
|

Does the trematode Centrocestus formosanus affect the locomotory activity of the mollusc Melanoides tuberculatus?

Abstract: BackgroundMelanoides tuberculatus (Müller, 1774) (Thiaridae), an introduced gastropod mollusc with a wide geographical distribution in the Neotropics, is the intermediate host of the trematode Centrocestus formosanus (Nishigori, 1924) (Heterophyidae). This parasite is considered to be pathogenic to humans. The aim of the present work was to evaluate the locomotory activity of uninfected M. tuberculatus compared with those naturally infected with C. formosanus.FindingsThe locomotory activity of each mollusc was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Centrocestus formosanus Nishigori, 1924, a species considered of zoonotic importance, was introduced in the Americas within its host snail Melanoides tuberculata. It has been reported from Brazil [43][44][45][46][47], Colombia [48], Peru [50] and Venezuela [51]. The life-cycle includes naturally infected fish (metacercariae in the gills) and birds (adults in the intestine) and experimental infections were performed with G. gallus [45] (Table 1).…”
Section: Taxonomy and Life Cyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Centrocestus formosanus Nishigori, 1924, a species considered of zoonotic importance, was introduced in the Americas within its host snail Melanoides tuberculata. It has been reported from Brazil [43][44][45][46][47], Colombia [48], Peru [50] and Venezuela [51]. The life-cycle includes naturally infected fish (metacercariae in the gills) and birds (adults in the intestine) and experimental infections were performed with G. gallus [45] (Table 1).…”
Section: Taxonomy and Life Cyclesmentioning
confidence: 99%
“…The heterophyid trematode C. formosanus was introduced into Brazil with the gastropod Melanoides tuberculata, which has a wide geographic distribution in the Neotropics [47]. This species, which is considered to have zoonotic potencial, is able to alter the locomotory activity of its snail host regardless of the standard length [47].…”
Section: Behavior and Ecotoxicologymentioning
confidence: 99%
“…Pleurolophocercous cercariae were firstly recorded in M. tuberculata in the state of Rio de Janeiro (Boaventura et al, 2002;Bogéa et al, 2005;Thiengo et al, 2001) and later, similar larvae were found in Minas Gerais state, which were identified as the heterophyid trematode Centrocestus formosanus (Nishigori, 1924), for the first time in Brazil (Pinto and Melo, 2010). This species was also found parasitizing M. tuberculata in the Federal District (Paula-Andrade et al, 2012) and in the states of Rio Grande do Norte (Pinto and Melo, 2012c) and Rio de Janeiro (Santos et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…To date, it has been reported from 19 states and from the Federal District (Fernandez et al, 2003;Rocha-Miranda and Martins-Silva, 2006;Santos et al, 2013;Thiengo et al, 2007). The species is associated with ecological problems, such as the modification of the community structure caused by the high population densities that it may reach (Santos and Eskinazi-Sant'Anna, 2010;Santos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, new studies have reported the interaction of C . formosanus with various hosts, both naturally-infected snails [ 16 ] and experimentally-infected fish, amphibians and rodents [ 17 20 ]. Moreover, several studies related to treatment, control, and monitoring strategies for aquatic ecosystems were performed in the last several years [ 21 24 ].…”
Section: Introductionmentioning
confidence: 99%